The use of chronobiotics in the resynchronization of the sleep/wake cycle : therapeutical application in the early phases of Alzheimer's disease - Cardinali, Daniel Pedro (2011)
Fil: Cardinali, Daniel Pedro. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Departamento de Docencia e Investigación; Argentina